Emotional Verbs of Angry in Javanese Ngoko: Semantic Studies - Astri, Nanda Dwi; Mulyadi, Mulyadi (RIRAI Publisher, 2024)
Emotional verbs are verbs that express a person's emotional or psychological state or action. This study uses the Natural Semantic Metalanguage (MSA) theory. MSA theory is a study of lexical semantics. The basic assumption of this theory is that complex meanings can be described using simpler configurations of meaning elements until they cannot be further described. The MSA theory used in this study is a framework for mapping meaning using basic components that can be understood by all native speakers. MSA theory is able to explain the lexical meaning of stative emotional verbs, while polysemy is used to understand emotional verbs in Ngoko Javanese with more than one meaning depending on the context of their use. Angry emotional verbs express a person's emotional or psychological actions in a state of anger. The purpose of this study is to describe angry emotional verbs in Ngoko Javanese. The importance of this research on angry emotional verbs in Ngoko Javanese is to see how the expression of angry emotional verbs in Javanese people who are known for being graceful, gentle and calm also has several verb expressions that express angry emotions. The emotional verbs of anger in Ngoko Javanese are ngamuk, greget, nesu, muring, ngelusuk, ngepruk, and ngerasa. This study takes the object of semantic study on the verb